Answers

2015-01-04T18:56:11+05:30
A+1=(a-1)/3-2a. (a+1)(3-2a)=a-1. 3a-2a²+3-2a=a-1. 3a-2a-a-2a²=-1-3. -2a²=-4. -2×2=-4. -4=-4. Lhs =Rhs. Hence proved.
0
not good
Is it unclear
I wrote in different lines but still it appears so
I've added a full stop after each step to give the least level of organization
2015-01-04T22:27:47+05:30
We have a²=2
         ⇒ a²-1= 2-1
         ⇒ (a+1)(a-1) = 1
         ⇒ (a+1) =1/(a-1)
RHS= (a-1)/(3-2a)
       = (a-1)/(2+1-2a)
       = (a-1)/ (a²+1-2a)       as  a²=2
       = (a-1)/(a-1)²
       = 1/(a-1)
       = a+1= LHS
    
0